2011
DOI: 10.1186/1745-6673-6-28
|View full text |Cite
|
Sign up to set email alerts
|

A case study on co-exposure to a mixture of organic solvents in a Tunisian adhesive-producing company

Abstract: Objectivesto assess environmental and biological monitoring of exposure to organic solvents in a glue-manufacturing company in Sfax, Tunisia.MethodsExposure of volunteer workers, in the solvented glue-work-stations, in the control laboratory and in the storage rooms of the finished products, was assessed through indoor-air and urine measurements. Informed consent of the workers was obtained.Results and discussionThe exposure indexes were found with high values in the solvented workshop as well as in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It has also been reported that the toluene concentration in urine was a more sensitive biomarker than hippuric acid [ 33 ]; however, many studies have found an association between metabolites in the urine and the concentration of toluene [ 33 , 34 ]. Therefore, it was widely used as a toluene-exposure biomarker [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the toluene concentration in urine was a more sensitive biomarker than hippuric acid [ 33 ]; however, many studies have found an association between metabolites in the urine and the concentration of toluene [ 33 , 34 ]. Therefore, it was widely used as a toluene-exposure biomarker [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of solvents is widespread in the region of Sfax, especially in the shoe and leather industry (38), semen quality was not affected in the solvent-exposed group. Duration and intensity of solvent exposure, which are determining for their impact on reproductive function, were not assessed in our study.…”
Section: Discussionmentioning
confidence: 83%